2019
DOI: 10.1007/s10895-019-02405-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Stoichiometry of Metal/Ligand Complex by Coupling Spectroscopy and Modelling: a Comprehensive Study on Two Fluorescent Molecules Specific to Lead

Abstract: Two new chemosensors for lead (II) were synthesized based on 5-((anthracen-9-ylmethylene) amino)quinolin-10-ol (ANQ): (10-(8-hydroxyquinolin-5-ylimino)methyl)anthracen-9-yl)methyl methacrylate (ANQ-MMA) and ((10-((4-vinylbenzoloxy)methyl)anthracen-9yl)methyleneamino)quinoline-8-ol (ANQ-ST). Complexation of those molecules with Pb 2+ was studied at room temperature using UV-Visible absorption and fluorescence spectroscopies. Thanks to the UVvisible absorption spectroscopy it appeared that ANQ-MMA formed 1:1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The impact of the composition of the IIPs was evaluated through fluorescence measurements. In the preliminary study of ANQ-ST, we showed that this polymerizable fluoroionophore answers in a "turnon" mode to the presence of Pb(II) [32]. Its relative fluorescence signal linearly increased upon Pb(II) addition before reaching saturation.…”
Section: Impact Of the Pb(ii)-iips Composition On Their Binding Prope...mentioning
confidence: 92%
See 2 more Smart Citations
“…The impact of the composition of the IIPs was evaluated through fluorescence measurements. In the preliminary study of ANQ-ST, we showed that this polymerizable fluoroionophore answers in a "turnon" mode to the presence of Pb(II) [32]. Its relative fluorescence signal linearly increased upon Pb(II) addition before reaching saturation.…”
Section: Impact Of the Pb(ii)-iips Composition On Their Binding Prope...mentioning
confidence: 92%
“…AgNO3, CaCO3, ZnSO4 and NaNO3 were purchased from Fisher Scientific (Analytical grade), CdSO4, Co(NO3)2 and CuSO4 from Merck (pro analysis grade), Pb(NO3)2 from Carlo Erba (Analytical grade). The functional fluorescent monomer ANQ-ST was prepared according to our previous study [32]. Pb(II) complexation with ANQ-ST was studied at 80°C, the temperature of polymerization, in different solvents: DMSO, DMSO-MeOH (1:1, v-v) and DMSO-ACN(1:1, v/v).…”
Section: Reagents and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation